Concomitant presentation of carpal tunnel syndrome and trigger finger - Rottgers, Stephen A; Lewis, Davis; Wollstein, Ronit A (Journal of Brachial Plexus and Peripheral Nerve Injury, 2009)
Background Carpal tunnel syndrome (CTS) and trigger finger (TF) are common conditions that may occur in the same patient. The etiology of most cases is unknown. The purpose of this study was to evaluate the rate of concomitant occurrence of these two conditions at presentation and to compare the concomitant occurrence in normal and diabetic patients.Methods One-hundred and eight consecutive subjects presenting to our hand clinic with CTS and/or TF were evaluated. The existence of both of these conditions was documented through a standard history and physical examination. The definition of trigger finger was determined by tenderness over the A1 pulley, catching, clicking or locking. CTS was defined in the presence of at least two of the following: numbness and tingling in a median nerve distribution, motor and sensory nerve loss (median nerve), a positive Tinel’s or Phalen’s test and positive electrophysiologic studies.Results The average age of the participants was 62.2 ± 13.6 years. Sixty-seven patients presented with symptoms and signs of CTS (62%), 41 (38%) subjects with signs and symptoms of TF. Following further evaluation, 66 patients (61%) had evidence of concomitant CTS and TF. Fifty-seven patients (53% of all study patients) had diabetes. The rate of subjects with diabetes was similar among the groups (p = 0.8, Chi-square test).Conclusion CTS and TF commonly occur together at presentation though the symptoms of one condition will be more prominent. Our results support a common local mechanism that may be unrelated to the presence of diabetes. We recommend evaluation for both conditions at the time of presentation.